2020
DOI: 10.3390/rs12050806
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Cross Calibration and Validation Using 4 Angle BRDF Model between Landsat 8 and Sentinel 2A

Abstract: This work describes a proposed radiometric cross calibration between the Landsat 8 Operational Land Imager (OLI) and Sentinel 2A Multispectral Instrument (MSI) sensors. The cross-calibration procedure involves (i) correction of the MSI data to account for spectral band differences with OLI and (ii) normalization of Bidirectional Reflectance Distribution Function (BRDF) effects in the data from both sensors using a new model accounting for the view zenith/azimuth angles in addition to the solar zenith/view angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…They found that the solar and view geometries were best defined in the Cartesian coordinates to preserve the nature of the data and to achieve a robust fit for the BRDF model. Moreover, the four-angle multi-linear interaction model provided the best BRDF model categorization, and after normalization, the estimated temporal stability was better than 3% over Libya 4 [20]. Considering the research of Farhad et al, conversion of the angles from Spherical to the Cartesian domain and developing an empirical BRDF model using four angles rather than just two angles can be contributed as improvement features in the absolute calibration model.…”
Section: Required Improvement In the Absolute Calibration Modelmentioning
confidence: 94%
“…They found that the solar and view geometries were best defined in the Cartesian coordinates to preserve the nature of the data and to achieve a robust fit for the BRDF model. Moreover, the four-angle multi-linear interaction model provided the best BRDF model categorization, and after normalization, the estimated temporal stability was better than 3% over Libya 4 [20]. Considering the research of Farhad et al, conversion of the angles from Spherical to the Cartesian domain and developing an empirical BRDF model using four angles rather than just two angles can be contributed as improvement features in the absolute calibration model.…”
Section: Required Improvement In the Absolute Calibration Modelmentioning
confidence: 94%
“…An absolute calibration BRDF model deriving linear and quadratic functions of the solar zenith angle was developed [27] using Libya 4. To fully account for the complexity of the BRDF effects, the BRDF model was developed including all the four angles as derived by Farhad et al [28] This model converts the view and solar angles from a spherical coordinate basis to a linear Cartesian basis and obtains a TOA reflectance of the surface as a continuous function of independent variables. Kaewmanee [29] further extended the model developed by Farhad et al, using an interaction term, which characterized the BRDF model well, with better uncertainty after normalization.…”
Section: Bidirectional Reflectance Distribution Function Normalizationmentioning
confidence: 99%
“…The mean cross-calibration for the trend-to-trend approach was calculated by taking an average of the blue data in Figure 18 and, for the Libya 4 coincident scene, pairs approaching the mean cross-calibration gain were calculated by taking the average of the red datapoints in Figure 18. The black data in Figure 19 were derived by Farhad et al [28] for the cross-calibration of OLI and MSI sensors using PICS, where the error bars represent the uncertainty derived, which was approximately 6.8%. For two perfectly calibrated sesnors, the value of the cross-calibration gain ratio is expected to be unity.…”
Section: Cluster-based Trend Totrend Cross-calibration Vs Traditional Pics-based Cross-calibration Gain Along With the Associated Uncertamentioning
confidence: 99%
“…In the military field, Melvin et al [5] applied it to remote detection of mines and improvised explosive devices. In the aviation field, Yeom et al [6] used it to detect thin clouds on the ground, which improved the efficiency of determining thin cloud pixels; Farhad et al [7] used it to develop a new cross calibration technology for satellite sensors, so as to improve the data coordination between them. In the marine field, aval et al [8] used it to improve the target recognition of the underwater environment.…”
Section: Introductionmentioning
confidence: 99%